2007
DOI: 10.1002/jemt.20544
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of S100 protein in the nervous system of the adult zebrafish (Danio rerio)

Abstract: S100 proteins are EF-hand calcium-binding protein highly preserved during evolution present in both neuronal and non-neuronal tissues of the higher vertebrates. Data about the expression of S100 protein in fishes are scarce, and no data are available on zebrafish, a common model used in biology to study development but also human diseases. In this study, we have investigated the expression of S100 protein in the central nervous system of adult zebrafish using PCR, Western blot, and immunohistochemistry. The ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
4
26
0
2
Order By: Relevance
“…In any case, the ventricular contact is critical in maintaining NSC activity in vertebrates (Kaslin et al, 2009). The pattern of distribution of Sox2 in the ventricular walls is similar to that reported for S100 protein in the brain of adult zebrafish (Germanà et al, 2008). S100β is used as the standard marker for mature nongerminal astrocytes (Marz et al, 2010), and it should be noted that S100β‐expressing astrocytes have been reported to divide in the adult brain (Ihrie and Alvarez‐Buylla, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…In any case, the ventricular contact is critical in maintaining NSC activity in vertebrates (Kaslin et al, 2009). The pattern of distribution of Sox2 in the ventricular walls is similar to that reported for S100 protein in the brain of adult zebrafish (Germanà et al, 2008). S100β is used as the standard marker for mature nongerminal astrocytes (Marz et al, 2010), and it should be noted that S100β‐expressing astrocytes have been reported to divide in the adult brain (Ihrie and Alvarez‐Buylla, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Although fish species show intense labelling for the cytoskeleton‐associated calcium binding protein, S100 (present study; Germanà et al. ; Lazzari et al. ), upon comparison of zebrafish with guppy, only the intracranial olfactory nerve and olfactory nerve layer displayed similar immunostaining intensities in the two species, whereas other parts of the olfactory system were less stained in zebrafish.…”
Section: Discussionmentioning
confidence: 45%
“…The pieces were cut in serial frontal, horizontal, and sagittal sections 10-lm thick, and collected on gelatin-coated microscope slides. The sections were then processed for indirect peroxidase immunohistochemistry as previously described (Germanà et al 2008). In brief, deparaffinized and rehydrated sections were rinsed in TrisHCl buffer (0.05 M, pH 7.5) containing 0.1% bovine serum albumin and 0.2% Triton-X-100.…”
Section: Localization Of Trkb and Bdnf Immunohistochemistrymentioning
confidence: 99%